The Effects of a Brain Capacity Development Program on Cognitive Function in Elderly with Mild Cognitive Impairment - Wichaidit, Arisya; Prewnim, Arpakorn (Journal of health and health management, 2025)
The study was quasi-experimental research aimed at examining the effects of a brain capacity development program on cognitive function in the elderly with mild cognitive impairment. The sample consisted of 40 elderly individuals with mild cognitive impairment. Data were collected at the Women’s Homeless Shelter in Thanyaburi over a period of six weeks. The instruments used consisted of (1) The Thai Mental State Examination (TMSE) form for screening mental state. (2) The personal data questionnaire and the Montreal Cognitive Assessment (MoCA) for assessing personal information and dementia and (3) The Brain Capacity development program. The data were analyzed using descriptive statistics, chi-square statistics, Non-parametric Wilcoxon statistics, and the Mann-Whitney U test, with a significance level of .05. The results were found that the mean cognition score of the experimental group after participating in the brain capacity development program were significantly higher than before the intervention at a statistical significance level of .05, Additionally, the mean cognitive score of the experimental group were significance higher than the control group, who received standard care, at the same statistical significance level.